The Dilemma of Inclusive Education: Inclusion for Some or Inclusion for All - Leijen, Äli; Arcidiacono, Francesco; Baucal, Aleksandar (Frontiers in Psychology, 2021)
In this paper, we intend to consider different understandings of inclusive education that frame current public and professional debates as well as policies and practices. We analyze two - somewhat opposing - discourses regarding inclusive education, namely the ‘inclusion for some’ - which represents the idea that children with special needs have a right to the highest quality education which can be delivered by specially trained staff, and the ‘inclusion for all’ - which represents the idea that all children regarding their diverse needs should have the opportunity to learn together. To put the two discourses in a dialogical relation, we have reconstructed the inferential configurations of the arguments of each narrative, to identify how the two definitions contribute to position children with and without special needs and their teachers. The results show the possibilities to bridge the two narratives, with respect to the voices they promote or silence, the power relations they constitute, and the values and practices they enact or prevent.